Efficacy of Carfilzomib, Lenalidomide, and Dexamethasone for Extramedullary Intracranial Localization of Multiple Myeloma - Mele, Giuseppe; Pastore, Domenico (Case Reports in Hematology, 2018)
EMD of myeloma usually occurs several years after diagnosis and is associated with a very poor OS of <6 months due to the fact that there are no efficient treatment options. In rrMM with EMDs, the most effective treatment is a lymphoma-like polychemotherapy regimen such as PACE, Dexa-BEAM, and HyperCVAD followed by ASCT or allogeneic SCT. RT of soft-tissue plasmacytoma is the further treatment choice and results in a high rate of local control and a prolonged disease-free survival. We report the case of a 41-year-old man affected by ultra-high-risk symptomatic IgAλ MM with extramedullary intracranial soft-tissue relapsed after VTD-PACE followed by ASCT. The salvage program with KRd regimen determines a second biochemical and haematological remission and a gradual reduction in size of the extramedullary intracranial soft-tissue even in the absence of local aggressive radiotherapy, suggesting that carfilzomib and lenalidomide together could be effective also in this critical situation.